2004
DOI: 10.1017/s002193200300645x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Health Services Use for Respiratory Illness in Indonesian Children: Implications for Policy

Abstract: Respiratory illness continues to be a leading cause of paediatric morbidity and mortality in Indonesia. The Indonesian government is moving towards a more managed care-based approach as it reforms its health care system following the 1997 financial crisis. In order to better design contractual relationships between the payor and different providers, there needs to be a better understanding of the patterns and predictors of health services utilization for respiratory illness. This study uses the Indonesia Demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 21 publications
3
17
1
Order By: Relevance
“…However, an increasing body of empirical evidence indicates that children in low and middle income countries were more likely to receive care if their mothers/caregivers perceived illness to be serious [24, 37, 40–46]. We found that perceived cause of acute diarrhea was not a predictor for health-seeking, corroborating several other studies [24, 40, 43, 44]. …”
Section: Discussionsupporting
confidence: 88%
“…However, an increasing body of empirical evidence indicates that children in low and middle income countries were more likely to receive care if their mothers/caregivers perceived illness to be serious [24, 37, 40–46]. We found that perceived cause of acute diarrhea was not a predictor for health-seeking, corroborating several other studies [24, 40, 43, 44]. …”
Section: Discussionsupporting
confidence: 88%
“…One of the reasons for slow progress in achieving MDG-4 in many LMICs is the socio-economic inequities existing in these countries. These inequities may also affect access to and utilization of available health care services [13]–[15], time taken in seeking of medical care as well as selection of appropriate health care provider [16][21] for acute childhood illnesses. Studies from various countries suggest that health care seeking is inappropriate and health services are often under-utilized during childhood illnesses [13], [15], [20], [24], [26].…”
Section: Introductionmentioning
confidence: 99%
“…The perception of illness severity by the caretaker has been strongly associated with healthcare seeking; other associated factors are the child's age, household size, maternal literacy, religion, health insurance coverage, family income and geographical location. [10][11][12][13][14] To our knowledge, the information focused on children's healthcare utilization in Mexico comes from national surveys. The National Survey of Health (ENSA 2000) 15 and National Health and Nutrition Survey 2006 (ENSANUT 2006) 16 reported that the age-adjusted immunization rates of children aged 1 to 2 years were 78.4% and 84.7% respectively, and the 2-week prevalence of acute respiratory infection was 13% and acute diarrhea 15%.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with other studies in which some factors such as the mother's literacy and family income among others are related to healthcare use. [10][11][12][13][14] In our analysis, the covariates mother living with a partner and having paid work, can be interpreted as the possibility of regular income. Also, we observed that if the child suffered from a disease other than diarrhea and acute respiratory infection, this had a strong influence on the use of curative care.…”
mentioning
confidence: 99%